Odpowiedzi

2009-12-28T22:43:41+01:00
A)
y=ln(cos½x)²
y'=2ln(cos½x)* (1/(cos½x))*½=ln(cos½x)* (1/(cos½x))

b)
y=xarctgx - ½ln(x² +1 )
y'=arctgx+x*(1/(1+x²)) -½*(1/(x² +1)) *2x=
=arctgx+x*(1/(1+x²))-x(1/(x² +1))=arctgx
Najlepsza Odpowiedź!
2009-12-28T23:39:16+01:00
A)
(ln x)' = 1/x
(x²)' = 2x
(cos x)' = -sin x
y=ln(cos½x)² - funkcja złożona powyższych
y' = 1/(cos½x)² * [(cos½x)²]' = 1/(cos½x)² * 2 * (cos ½ x)' =
1/(cos½x)² * 2 * (-sin ½ x) * (½ x)' = 1/(cos½x)² * 2 * (-sin ½ x) * ½ =
-sin ½ x / (cos½x)² = -tg ½ x / cos½x

b) y=xarctgx - ½ln(x² +1)
Stosujemy wzór na pochodną iloczynu oraz na pochodną funkcji złożonej:
y' = x' * arctgx + x * (arctgx)' -½ * 1/(x² +1) * 2x =
arctgx + x / (1 + x²) - x / (x² +1) = arctgx